Letter from the Editor - Edmundo Mora (Asociación Colombiana de Profesores de Ingles, 2016)
The Editorial Committee has been working hard to have this edition ready for the Annual ASOCOPI congress which this tiem will take place in October in Bogotá. The Committee thinks that this congress is the perfect occasion to exchange ideas about academic matters and to distribute HOW to our subscribers and English teachers from all over the country who attend these academic events.